Numerical analysis of the equipment position influence on the premises thermal regime under gas infrared emitter operation and mixed convection conditions; Journal of Physics: Conference Series; Vol. 2119 : The XXXVII Siberian Thermophysical Seminar (STS37) 2021 - Borisov B. V. Boris Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Maksimov V. I. Vyacheslav Ivanovich; Nagornova T. A. Tatiana Aleksandrovna; Vyatkin A. V. Aleksandr Vitaljevich (2021, 2021)
Title screen